Sustainable practices in manufacturing: How green innovation drives financial performance with gender diversity and CSR as moderators - Haryanto, Hery; Jennifer, Fion; Marheni, Dewi Khornida (Journal of Accounting and Investment, 2026)
Research aims: This research analyzes how green innovation strategies influence the financial performance of manufacturing firms in Indonesia, with Corporate Social Responsibility (CSR) and gender diversity as moderators.Design/Methodology/Approach: A quantitative approach using secondary data from 70 manufacturing firms listed on the Indonesia Stock Exchange (2018–2022) was applied. Ordinary Least Squares (OLS) regression was conducted in Stata, with purposive sampling based on specific criteria.Research findings: Green innovation and gender diversity significantly enhance financial performance. CSR, however, shows no significant direct effect, and neither CSR nor gender diversity significantly moderates the relationship between green innovation and financial performance.Theoretical contribution/Originality: The study makes three contributions. First, it examines CSR and gender diversity simultaneously as independent factors and moderators, highlighting their differential roles in emerging markets. Second, it identifies boundary conditions, showing that green innovation delivers benefits mainly when organizational capabilities are sufficient, challenging the generalizability of Western-based theories. Third, it offers insights into why stakeholder mechanisms may be less effective in contexts with weak enforcement and symbolic compliance, refining theoretical understanding in emerging-market settings.Practitioner/Policy implication: Managers and policymakers should treat gender diversity as a strategic asset to enhance performance, while CSR initiatives should be carefully designed and consistently implemented to add genuine value rather than symbolic compliance.